Modalities Used By Indonesian and American In Political Debate Discourse (A Comparative Study) - Rabiatul Adawiyah (Jurnal Adabiyah: Humanities and Islamic Studies, 2017)
Modalities in Political Debate Discourse. This study is aimed at investigating modalities used by the speakers of political debate in two countries; Indonesia and USA. This study is a comparative study which uses descriptive qualitative in analysing and displaying data. Both data were taken from youtube.com on April 2014. Firstly, the result of this study shows that the speakers of political debate in Indonesia and America used three values of modality; high, median and low value of modality. A way of choosing modalities does not only with a correct grammar; but also from the functional point of view. Politicians tended to use high value of modality to show their high commitment toward opinion or argument, and presenter tended to use median and low values of modality in offering the other speakers rather than the high value of modality; although the presenter actually wanted to state a requirement that should be followed. Lastly, the English speakers are more explicit to put their selves as the subject of assessment rather than the Indonesian speakers of political debate.